An injectable filler capable of stimulating collagen regeneration remodeling, and a preparation method and application thereof
Patent Information
- Application Number
- CN202311859950.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-31
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-12-31
AI Technical Summary
这类填充剂的即刻填充效果一般是基质材料的物理支撑作用,基质材料吸收较快,后续新生胶原产生较慢,中间会出现一段无填充效果的空窗期,影响美观
[0037]1、本发明提供的微球、纤维和基质材料填充剂,皮下注射后既可以产生即刻填充效果,还可以促进巨噬细胞由M1型转变为M2型,高效刺激胶产生长期填充效果,而且即刻和长期填充之间不存在空窗期,始终保持良好的填充效果;
Smart Images

Figure BDA0004643307270000081 
Figure BDA0004643307270000091 
Figure BDA0004643307270000101
Abstract
Description
Technical Field
[0001] This invention belongs to the fields of medicine and cosmetic filler materials, specifically relating to an injectable filler that can stimulate collagen regeneration and remodeling, its preparation method, and its application. Background Technology
[0002] Injectable fillers are a cosmetic treatment that improves and repairs skin shape and contours by directly injecting them into the skin or soft tissue. Implantation of biomaterials triggers a unique foreign body reaction, which mainly involves three processes: protein absorption, cell aggregation, and fibrous encapsulation. When biomaterials are implanted subcutaneously, the body automatically recognizes them as foreign bodies, triggering a subclinical foreign body inflammatory response, leading to material encapsulation, fibrosis, and ultimately collagen deposition. During this process, pro-inflammatory M1 macrophages aggregate and phagocytose apoptotic granulocytes after processing the foreign body. Macrophages are reprogrammed from the pro-inflammatory M1 phenotype to the anti-inflammatory M2 phenotype. The M2 phenotype stimulates fibroblasts to proliferate and secrete collagen. Collagen deposition also increases the risk of granulomas and scarring. Shortening the M1 macrophage transition time and promoting the conversion to M2 helps reduce inflammation, promotes collagen regeneration, and improves the filling effect. The dermis of adults is mostly composed of type I and type III collagen, with a ratio of approximately 4:1.
[0003] Existing fillers are irregular gels, granules, or spheres, and most cause an inflammatory response within a few months, stimulating the body to produce some collagen. Prolonged inflammation can lead to inflammatory aging, granulomas, and excessive scarring. The immediate filling effect of these fillers is generally due to the physical support of the matrix material. The matrix material is absorbed quickly, while subsequent new collagen production is slow, resulting in a window of no filling effect, affecting aesthetics. Long-term filling effects mainly depend on the subsequent production of new collagen. An imbalance in the ratio of type I and type III collagen during collagen deposition can lead to keloid formation. If the newly generated collagen consists only of dense, firm type I collagen or has an excessively high proportion of easily lost type III collagen, it can cause facial stiffness, keloid formation, and wrinkles due to the loss of type III collagen.
[0004] Therefore, reducing inflammation, effectively stimulating collagen production, and reshaping the ratio of type I and type III collagen can achieve a more uniform filling effect, giving the newly formed collagen a ratio closer to the composition of normal skin, reducing the formation of foreign body granulomas and keloids, making the facial filling effect more lasting, reducing the number of injections, resulting in more natural expressions, no swelling, no stiffness, and less wrinkles. Summary of the Invention
[0005] Purpose of the invention: To address the problems existing in the prior art, this invention provides an injectable filler that can stimulate collagen regeneration and remodeling. This invention adds specific microspheres and fibers to a matrix gel to form a special spatial structure, which can produce an immediate filling effect after subcutaneous injection. As the matrix gel is absorbed, the microspheres and fibers are gradually exposed as foreign body stimuli, causing only short-term mild inflammation in the early stage and reducing the risk of granulomas. It significantly increases the total amount of collagen and remodels the ratio of stimulated collagen type I and type III, making it closer to normal skin.
[0006] The present invention also provides a method for preparing and applying the injectable filler that can stimulate collagen regeneration and remodeling.
[0007] Technical Solution: To achieve the above objectives, the present invention provides an injectable filler that can stimulate collagen regeneration and remodeling, characterized in that the filler is mainly composed of microspheres, fibers, and matrix materials; the materials of the microspheres and fibers are one or more of polycaprolactone, polylactic acid, polylactic-co-hydroxyacetic acid copolymer, polyvinyl alcohol, polytrimethylene carbonate, hydroxyapatite, polymethyl methacrylate, or their derivatives; the matrix material is one or more of hyaluronic acid, sodium carboxymethyl cellulose, hydroxypropyl cellulose, sodium alginate, polyethylene glycol, or their derivatives.
[0008] Preferably, the microspheres are made of polycaprolactone, polylactic acid, or polytrimethylene carbonate, and the fibers are made of polycaprolactone or polytrimethylene carbonate; the matrix material is hyaluronic acid.
[0009] The microspheres are spherical or near-spherical in shape, with a particle size of 20–100 μm; the fibers are rod-shaped or near-rod-shaped, with a diameter of 1 μm–200 μm and a length of 10 μm–1000 μm; the matrix material is mainly hydrogel.
[0010] Preferably, the microspheres have a particle size of 25–60 μm; the fiber diameter is 50 μm–150 μm; and the fiber length is 300 μm–700 μm.
[0011] The mass ratio of microspheres to fibers is 1:1 to 100:1; the mass ratio of microspheres to gel matrix is 1:10 to 1:100.
[0012] Preferably, the mass ratio of microspheres to fibers is 10:1 to 50:1; and the mass ratio of microspheres to gel matrix is 1:20 to 1:50.
[0013] Furthermore, the filler may include water, isotonic agents, pH adjusters, and analgesics.
[0014] The preparation method of the injectable filler that can stimulate collagen regeneration and remodeling according to the present invention includes the following steps:
[0015] Microsphere preparation methods include emulsification-crosslinking, spray drying, electro-spraying, or microfluidics;
[0016] Fiber preparation methods include electrospinning, near-field electrospinning, melt spinning, extrusion spinning, grinding, air jet milling, microfluidic spinning, or bioprinting.
[0017] The methods for preparing matrix materials include physical crosslinking, chemical crosslinking, free radical homopolymerization or copolymerization, radiation method or photopolymerization;
[0018] The fibers and microspheres are added to the matrix material and thoroughly mixed to obtain the final product.
[0019] Preferably, the microspheres are prepared by emulsification-crosslinking; the fibers are prepared by electrospinning or extrusion spinning; and the gel matrix is prepared by chemical crosslinking.
[0020] Furthermore, the method for preparing the injectable filler that can stimulate collagen regeneration and remodeling includes the following steps:
[0021] (1) Microsphere preparation: Polytrimethylene carbonate was dissolved in an organic solvent and ultrasonically mixed to form an oil phase. The oil phase was added dropwise to a polyvinyl alcohol aqueous solution and emulsified by stirring at 300-800 rpm / min for 2-8 hours. After the organic solvent in the solution was evaporated, the microspheres were washed, freeze-dried, and passed through a sieve.
[0022] (2) Fiber preparation: Polycaprolactone solution and polytrimethylene carbonate solution are mixed together to form the required electrospinning suspension. The mixed suspension is electrospinned at a working distance of 10-20 cm, a voltage of 8-13 kV, and a syringe pump speed of 0.5-1.2 mL / h to obtain a fiber membrane. The electrospinned fiber membrane is frozen in liquid nitrogen for 10-20 minutes and broken into fibers with a high-speed stirrer. The fibers are then passed through a sieve to obtain the fibers.
[0023] (3) Matrix preparation: Weigh hyaluronic acid, dissolve it in sodium hydroxide solution, add 1,4-butanediol diglycidyl ether, heat at a constant temperature of 40-60℃, stir at a speed of 100-400 rpm / min for 1-4 hours to crosslink the gel, adjust the pH to neutral, dialyze to purify, freeze dry and then reconstitute to obtain the matrix.
[0024] (4) Mixing: Add the fibers and microspheres to the matrix and mix thoroughly to obtain the final product.
[0025] Furthermore, the method for preparing the injectable filler that can stimulate collagen regeneration and remodeling:
[0026] (1) Microsphere preparation: A certain mass of polytrimethylene carbonate was weighed and dissolved in dichloromethane, and ultrasonically mixed to form an oil phase. The oil phase was added dropwise to a 0.8-10% (w / w) aqueous solution of polyvinyl alcohol, and emulsified by stirring at 300-800 rpm / min for 2-8 hours. After the dichloromethane in the solution was evaporated, the microspheres were washed 3-5 times with pure water, freeze-dried, and passed through a sieve of a certain mesh size to obtain microspheres.
[0027] (2) Fiber preparation: Polycaprolactone solution and polytrimethylene carbonate solution of a certain concentration were prepared using dichloromethane as solvent. These two solutions were then mixed together at a certain volume ratio to form the desired electrospinning suspension. The mixed suspension was poured into a syringe, and electrospinning was performed at a working distance of 10–20 cm, a voltage of 8–13 kV, and a syringe pump speed of 0.5–1.2 mL / h to obtain a fiber membrane. The electrospun fiber membrane was frozen in liquid nitrogen for 10–20 minutes, then broken into fibers using a high-speed stirrer. The fibers were then passed through a sieve of a certain mesh size to obtain the fibers.
[0028] (3) Matrix preparation: Weigh a certain amount of hyaluronic acid and dissolve it in a 0.1–0.5 mol / L sodium hydroxide solution. Add 1–5% (w / w) of 1,4-butanediol diglycidyl ether and heat at a constant temperature of 40–60°C. Stir at 100–400 rpm / min for 1–4 hours to allow the gel to crosslink. Adjust the pH to neutral, purify by dialyzing with pure water, freeze-dry, and then reconstitute with PBS to obtain the matrix.
[0029] (4) Mixing: Add a certain mass of fiber and microspheres to the above matrix and stir thoroughly to obtain the final product.
[0030] The present invention relates to the application of injectable fillers that stimulate collagen regeneration and remodeling in medical aesthetics, plastic surgery, filling, and tissue defect repair.
[0031] Preferably, the injectable filler that can stimulate collagen regeneration and remodeling is used in the preparation of medical aesthetic, plastic surgery, filling and tissue defect repair materials.
[0032] All of the above materials can be selected based on the requirements of filling and degradation time, and can be non-crosslinked or biomaterials with different degrees of crosslinking and different molecular weights, according to existing technology reports. Crosslinking methods can employ existing preparation methods, such as physical crosslinking using light or heat, or chemical crosslinking using free radicals, ions, or other molecules. Crosslinking agents can be substances reported in existing technologies, such as polyisocyanates, polyamines, polyols, glycidyl ethers, and olefin monomers.
[0033] The preparation method of the injectable filler that can stimulate collagen regeneration and remodeling can employ existing preparation methods, including but not limited to the methods described above. To obtain microspheres and fibers of suitable particle size, existing sieving methods can be used, such as manual sieving, mechanical sieving, and air jet sieving.
[0034] The injectable filler that stimulates collagen regeneration and remodeling is characterized in that it may contain water, an isotonic agent, a pH adjuster, an analgesic, etc. The isotonic agent may be an existing osmotic pressure adjuster, such as physiological saline, glycerin, glucose, etc. The analgesic may be an existing drug, such as diclofenac sodium, lidocaine, flurbiprofen ester, parecoxib sodium, ketorolac tromethamine, and celecoxib, etc.
[0035] This invention prepares an injectable filler that stimulates collagen regeneration and remodeling. By incorporating microspheres and fibers of specific sizes into a matrix, it can significantly increase collagen content and regulate the ratio of type I and III collagen produced, making it closer to the elasticity of real skin, reducing the risk of granulomas, and achieving optimal filling effect. All materials in this invention use biocompatible and biodegradable raw materials, achieving a long-lasting and continuous stimulation of collagen production. Furthermore, the specific microspheres and fibers produce a significant synergistic effect in increasing total collagen volume. The filler prepared by this invention can be used in the preparation of cosmetics, tissue filling and repair, biological scaffolds, ophthalmology, drug sustained release and targeted drug delivery, and other fields such as cosmetics, pharmaceuticals, and medical aesthetics, showing broad application prospects.
[0036] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0037] 1. The microsphere, fiber and matrix material filler provided by the present invention can produce an immediate filling effect after subcutaneous injection, and can also promote the transformation of macrophages from M1 type to M2 type, effectively stimulating the gel to produce a long-term filling effect. Moreover, there is no gap between the immediate and long-term filling, and the filling effect is always maintained.
[0038] 2. The microspheres, fibers and matrix materials provided by this invention can promote the transformation of macrophages from M1 type to M2 type, producing only short-term mild inflammation in the early stage, reducing the risk of granulomas and keloids;
[0039] 3. The microspheres, fibers and matrix materials provided by this invention reshape the ratio of stimulated type I and type III collagen, making it closer to normal skin. It will not cause scar-like hard lumps in the skin due to excessive new type I collagen, nor will it cause wrinkles due to excessive new type III collagen loss over time, resulting in a more natural filling effect. Attached Figure Description
[0040] Figure 1 These are images of collagen fluorescence staining: microspheres + matrix (a), fibers + matrix (b), and microspheres + fibers + matrix (c). Detailed Implementation
[0041] The present invention will be further described below with reference to specific embodiments and accompanying drawings.
[0042] Unless otherwise specified, the experimental methods described in the embodiments are conventional methods; unless otherwise specified, the reagents and materials are commercially available.
[0043] The specific substances used in the examples and their sources are as follows:
[0044] Polycaprolactone (molecular weight 80,000-100,000, Shanghai Aladdin Biochemical Technology Co., Ltd., catalog number P579406);
[0045] Polylactic acid (molecular weight 80,000, Shanghai Maclean Biochemical Technology Co., Ltd., product number P875107);
[0046] Polytrimethylene carbonate (molecular weight 49,000-118,000, Wuhan Haishan Technology Co., Ltd., product number DG-T200);
[0047] Polyvinyl alcohol (molecular weight 1700-1800, Sinopharm Chemical Reagent Co., Ltd., item number 30153160);
[0048] Hyaluronic acid (molecular weight 200,000-400,000, Shanghai Maclean Biochemical Technology Co., Ltd., product number H909936);
[0049] Polyethylene glycol 1000, Sinopharm Chemical Reagent Co., Ltd.
[0050] Example 1
[0051] Preparation of microspheres
[0052] (1) Polycaprolactone microspheres: electro-spraying method
[0053] A 1% (w / w) polycaprolactone-chloroform mixed solution system was prepared and thoroughly dissolved by continuous stirring at room temperature for 12 hours. 4 mL of the polymer solution was drawn into a syringe with a needle tip inner diameter of 0.7 mm. The positive terminal of a high-voltage power supply was connected to the needle tip, and the negative terminal to the collecting device. Aluminum foil was attached to the collecting plate, and the syringe was fixed on the propellant pump. The propellant speed was set to 25 μL / min, the voltage to 15 kV, the receiving distance to 15 cm, and the room temperature to 20 °C. The propellant pump was started, and after droplets began to fall from the needle tip, the DC voltage was turned on. During the spraying process, the solvent evaporated. Ethanol was used to collect the product in the receiving section, and the mixture was stirred to allow the polycaprolactone to solidify and form microspheres. The product was collected by continuous electrospraying for 5 hours. The voltage was then adjusted to zero, the power was turned off, the product was collected, freeze-dried for 24 hours, and stored at 4 °C.
[0054] (2) Polylactic acid microspheres: microfluidic method
[0055] Weigh 20 mg of polylactic acid and dissolve it in 5 mL of ethyl acetate. Stir until fully dissolved to obtain the oil phase. Inject the oil phase and 5 mL of 0.1% PVA aqueous solution using a micropump to slowly mix them in a flow-focusing PDMS microfluidic chip (both phases flow rate 1 mL / 20 min). The collected mixture is slowly stirred for 5 min and then further sonicated for 5 min. The resulting emulsion is then stirred on a magnetic stirrer until the ethyl acetate has completely evaporated and solids precipitate. Filter to remove excess liquid, wash with pure water, freeze-dry for 24 h, and store at 4 °C.
[0056] (3) Polytrimethylene carbonate microspheres: emulsion-solvent evaporation method
[0057] 500 mg of polytrimethylene carbonate was dissolved in 10 mL of dichloromethane and ultrasonically mixed to form an oil phase. The entire oil phase was then added dropwise to 100 mL of a 3% (w / w) aqueous solution of polyvinyl alcohol. The mixture was stirred and emulsified at 300 rpm for 2 hours at room temperature. The dichloromethane in the solution was evaporated, and the mixture was washed three times with pure water, then freeze-dried and passed through a sieve of a certain mesh size to obtain polytrimethylene carbonate microspheres.
[0058] In this embodiment, the polycaprolactone microspheres, polylactic acid microspheres, and polytrimethylene carbonate microspheres can all be produced using emulsification-crosslinking, spray drying, electro-spraying, and microfluidics methods.
[0059] Example 2
[0060] Fiber preparation
[0061] (1) Polycaprolactone fiber: melt spinning method
[0062] The receiving distance of the screw extruder is set to 5 cm. The extruder temperature is heated to 150℃. After the temperature stabilizes, a 5% polycaprolactone dichloromethane solution is added and heated for 5 minutes to form a melt. The melt pump pressure is 200 MPa, the extrusion roller speed is 500 r / min, and the take-up motor speed is 1500 r / min. The melt exits the screw extruder and is sent to the spinneret assembly by a metering pump. It is extruded from the spinneret orifice with a diameter of 0.2 mm and forms a fine stream to obtain a spun film. It is then ground into fibers using a grinder. The fibers are then ground, cut, and sieved to determine the length and diameter.
[0063] (2) Polytrimethylene carbonate fiber: extrusion spinning method
[0064] A 10mL medical syringe was connected to a No. 9 needle with an inner diameter of 0.6mm. The needle was connected to a high-voltage power supply and placed horizontally. A metal plate wrapped in tin foil was used to receive the fibers in a direction perpendicular to the needle. A 12% (w / w) polytrimethylene carbonate dichloromethane solution was poured into the syringe. The electrospinning parameters were fixed as follows: voltage 15kV, receiving distance 10cm, feed rate 0.6ml / h, and humidity 30%. The mixture was dried at room temperature for 48h, then vacuum dried for 24h to obtain a polytrimethylene carbonate fiber membrane. The membrane was then broken into fibers using a high-speed stirrer, and its length and diameter were determined by stirring, cutting, and sieving.
[0065] (3) Polycaprolactone solution and polytrimethylene carbonate mixture fiber: A 10% polycaprolactone solution and a 10% polytrimethylene carbonate solution were prepared using dichloromethane as a solvent. These two solutions were then mixed together in a 1:1 volume ratio to form the desired electrospinning suspension. The mixed suspension was poured into a syringe, and electrospinning was performed at a working distance of 11 cm, a voltage of 9 kV, and a syringe pump speed of 0.8 mL / h to obtain a fiber membrane. The electrospinned fiber membrane was frozen in liquid nitrogen for 10–20 minutes, and then broken into fibers using a high-speed stirrer. The length and diameter were determined by stirring, cutting, and sieving.
[0066] In this embodiment, the polycaprolactone fiber, polytrimethylene carbonate fiber, polycaprolactone solution, and polytrimethylene carbonate or mixture can all be produced by electrospinning, near-field electrospinning, melt spinning, extrusion spinning, grinding, microfluidic spinning, bioprinting, etc.
[0067] Example 3
[0068] Preparation of gel matrix
[0069] (1) Preparation of hyaluronic acid matrix: Weigh 4g of hyaluronic acid and dissolve it in 50mL of 0.2mol / L sodium hydroxide solution. Add 200μl of 1,4-butanediol diglycidyl ether and heat at a constant temperature of 50℃. Stir at 100rpm for 1 hour to allow the gel to crosslink. Adjust the pH to neutral and purify by dialyzing with pure water using a dialysis bag with a molecular weight of 2000 for 24h. After freeze-drying, reconstitute with PBS (pH 7.4) to prepare a 5% wt hyaluronic acid matrix solution.
[0070] (2) Preparation of the polyethylene glycol matrix: 0.2% N,N-methylenebisacrylamide was added to a 15% polyethylene glycol aqueous solution and mixed uniformly at a volume ratio of 1:75. The mixture was then added to a three-necked flask equipped with a stirrer and a reflux condenser. The air in the flask was first pumped out, and then high-purity nitrogen was purged for 30 minutes to remove air from the system. Then, 2% wt ammonium persulfate was added, and high-purity nitrogen was purged for another 15 minutes. The mixture was stirred at 45°C for 2 hours. The resulting product was extracted with water, dried, and reconstituted to obtain a dry 5% wt polyethylene glycol gel.
[0071] In this embodiment, the hyaluronic acid matrix and polyethylene glycol matrix can be obtained by physical crosslinking, chemical crosslinking, free radical homopolymerization or copolymerization, radiation method, photopolymerization, etc.
[0072] Example 4
[0073] Effect of different sizes on the M1 / M2 ratio of macrophages
[0074] Using polytrimethylene carbonate microspheres from Example 1 (3), polycaprolactone solution and polytrimethylene carbonate mixed fibers from Example 2 (3), and hyaluronic acid matrix from Example 3 (1), the sizes of the microspheres and fibers were controlled by sieving, stirring, and cutting to separate microspheres and fibers of different sizes. The sizes were measured by ImageJ under a microscope. The three components were then mixed and stirred evenly in a mass ratio of 10:1:500.
[0075] Experimental Methods: Four weeks after subcutaneous injection of 100 μl of the material into the back of ICR mice (weighing 20 ± 2 g), the skin was peeled back, and skin tissue was harvested from the corresponding locations and immediately fixed with tissue fixative. After paraffin embedding, sections were prepared for immunofluorescence staining of macrophage-related markers CD86, CD68, and CD207. The tissue was observed and photographed under a fluorescence confocal microscope, and the average fluorescence intensity was calculated using ImageJ. The experimental results are shown in Table 1.
[0076] Table 1. Effects of different formulation ratios on the M1 / M2 ratio of macrophages
[0077] 25-60 50-150 300-700 0.565±0.19 25-60 50-150 10-300 2.421±0.68 25-60 50-150 700-1000 2.146±0.71 25-60 1-50 300-700 3.102±1.73 25-60 150-200 300-700 1.932±1.14 20-25 50-150 300-700 5.426±0.88 60-100 50-150 300-700 5.985±2.27
[0078] Table 1 shows that the microsphere diameter and fiber size have a significant impact on the M1 / M2 ratio. When the microsphere diameter is <25μm, the fiber diameter is <50μm, or the fiber length is <300μm, the M1 / M2 ratio is high, and the material is easily phagocytosed by M1 macrophages, which leads to difficulty in continuously stimulating subcutaneous collagen production. When the microsphere diameter is >60μm, the fiber diameter is >150μm, or the fiber length is >700μm, the M1 / M2 ratio is high, attracting too many M1 macrophages to fuse and form foreign body giant cells, causing inflammation. When the microsphere diameter is 25-60μm, the fiber diameter is 50-150μm, and the fiber length is 300-700μm, the M1 / M2 ratio is significantly the lowest, and the material promotes more macrophage polarization towards M2, resulting in a stronger ability to stimulate collagen.
[0079] Example 5
[0080] Effects of different prescription ratios on the M1 / M2 ratio of macrophages
[0081] The microspheres of Example 1 (3), the polytrimethylene carbonate mixture fibers of Example 2 (3) and polycaprolactone solution and polytrimethylene carbonate, and the hyaluronic acid matrix of Example 3 (1) were mixed and stirred evenly with the microsphere diameter (25-60μm), fiber diameter (50-150μm) and fiber length (300-700μm) controlled by mass ratios of 10:1:500, 10:2:500 and 30:1:500 respectively.
[0082] Experimental Methods: Four weeks after subcutaneous injection of 100 μl of the material into ICR mice (weighing 20 ± 2 g), the skin on the back was peeled off, and skin tissue was harvested from the corresponding locations and immediately fixed with tissue fixative. After paraffin embedding, sections were prepared for immunofluorescence staining of macrophage-related markers CD86, CD68, and CD207. The tissue was observed and photographed under a fluorescence confocal microscope, and the average fluorescence intensity was calculated using ImageJ. The experimental results are shown in Table 2.
[0083] Table 2. Effects of different formulation ratios on the M1 / M2 ratio of macrophages
[0084]
[0085] As shown in Table 2, the sustained M1 response around the biodegradable biomaterial is the cause of excessive scarring, while promoting the M2 response has been shown to be beneficial for the replacement of the material by host tissue. Different ratios of microspheres and fibers can significantly alter the M1 / M2 ratio of surrounding macrophages. When the ratio of microspheres + fibers + matrix is 10:1:500, the M1 / M2 ratio is significantly the lowest, and the macrophages around the material are predominantly polarized into M2-type macrophages, which helps reduce the generation of excessive scarring from the implanted material and continuously stimulates the production of subcutaneous collagen.
[0086] Example 6
[0087] Effects of different prescription combinations on inflammation
[0088] Using polytrimethylene carbonate microspheres from Example 1 (3), polycaprolactone solution and polytrimethylene carbonate mixed fibers from Example 2 (3), and hyaluronic acid matrix from Example 3 (1), the microsphere diameter (25-60 μm), fiber diameter (50-150 μm), and fiber length (300-700 μm) were controlled. Different combinations were prepared by mixing the microspheres and matrix at a mass ratio of 10:500, 1:500, and 10:1:500, and the following experiments were conducted.
[0089] Experimental Methods: Materials: ICR mice (weighing 20±2g) were subcutaneously injected with 100μl of the solution into their backs for 4 weeks. The skin was then peeled back, and skin tissue was harvested from the corresponding locations and immediately fixed with tissue fixative. After paraffin embedding, sections were prepared for immunofluorescence staining of the inflammatory factors IL-1β and TNF-α. The tissue was observed and photographed under a fluorescence confocal microscope, and the average fluorescence intensity was calculated using ImageJ. Experimental results are shown in Table 3.
[0090] Table 3. Effects of different prescription combinations on inflammation.
[0091] Microspheres + matrix 18.33±0.43 7.63±0.21 fiber + matrix 5.48±0.09 5.67±0.66 Microspheres + Fibers + Matrix 6.25±0.36 3.03±0.98
[0092] As shown in Table 3, M1 macrophages have strong phagocytic activity and can secrete a large number of acute inflammatory cytokines, such as IL-1β and TNF-α, thereby promoting acute inflammatory responses. Therefore, the sustained M1 response around the degradable biomaterial is the cause of excessive scar formation. After material implantation, the microsphere + matrix group had the highest level of inflammatory factors, while the fiber + matrix group had the lowest level of inflammation. The addition of fibers to the microsphere + fiber + matrix group significantly reduced the inflammation level compared to the microsphere alone group, thus lowering the risk of scarring at the filling site.
[0093] Example 7
[0094] Effects of different formulation combinations on total collagen and type I and type III remodeling
[0095] Using polytrimethylene carbonate microspheres from Example 1 (3), polycaprolactone solution and polytrimethylene carbonate mixed fibers from Example 2 (3), and hyaluronic acid matrix from Example 3 (1), the microsphere diameter (25-60 μm), fiber diameter (50-150 μm), and fiber length (300-700 μm) were controlled. Different combinations were prepared by mass ratio of microsphere + matrix 10:500, fiber + matrix 1:500, and microsphere + fiber + matrix 10:1:500 and stirred evenly. The following experiments were conducted.
[0096] Experimental Methods: Four weeks after subcutaneous injection of 100 μl of the material into the back of mice, the skin was peeled back, and skin tissue was harvested from the corresponding locations and immediately fixed with tissue fixative. After paraffin embedding, sections were prepared for immunofluorescence staining of type I and type III collagen. The tissue was observed and photographed under a fluorescence confocal microscope, and the average fluorescence intensity was calculated using ImageJ. The experimental results are shown in Table 4. Figure 1 As shown:
[0097] Table 4. Effects of different formulation combinations on total collagen and type I and type III remodeling.
[0098]
[0099]
[0100] As shown in Table 4, Type I and Type III collagen are the two main types of collagen in human skin. However, under pathological conditions, imbalanced collagen synthesis can lead to scar tissue formation. Hypertrophic scar tissue is mainly characterized by an excess of Type III collagen, while keloids are caused by disordered expression of both Type I and Type III collagen. Immunofluorescence staining images of Type I and Type III collagen are included. Figure 1 The results showed that one month after implantation, the collagen produced around the material was mainly type I collagen, with less type III collagen. Specifically, the ratio of type I collagen to type III collagen in the microsphere + matrix and fiber + matrix groups was 2.79:1 and 1.64:1, respectively. Figure 1 (a), (b)), while the ratio of type I collagen to type III collagen in the microsphere + fiber + matrix group is 3.87:1 ( Figure 1 (c) The ratio of type I collagen to type III collagen is approximately 4:1, close to the proportion found in normal skin, resulting in a more natural filling effect and facial expressions. Compared to microspheres + matrix and fibers + matrix, the combination of microspheres + fibers + matrix significantly stimulates collagen production in the skin, with the total collagen amount being 2.28 and 4.87 times that of microspheres + matrix and fibers + matrix, respectively. This significant increase in total collagen content allows for a more lasting filling effect. Furthermore, the ratio of type I collagen to type III collagen is approximately 4:1, close to the proportion found in normal skin, resulting in a more natural filling effect and facial expressions.
[0101] Example 8
[0102] Effects of different prescription combinations on keloids
[0103] Using polytrimethylene carbonate microspheres from Example 1 (3), polycaprolactone solution and polytrimethylene carbonate mixed fibers from Example 2 (3), and hyaluronic acid matrix from Example 3 (1), the microsphere diameter (25-60 μm), fiber diameter (50-150 μm), and fiber length (300-700 μm) were controlled. Different combinations were prepared by mixing the microspheres and matrix at a mass ratio of 10:500, 1:500, and 10:1:500, and the following experiments were conducted.
[0104] Experimental Methods: Four weeks after subcutaneous injection of 100 μl of the material into the back of mice, the skin was peeled back, and skin tissue was harvested from the corresponding locations and immediately fixed with tissue fixative. After paraffin embedding, sections were prepared for immunofluorescence staining for TGF-β and α-SMA. The tissue was observed and photographed under a fluorescence confocal microscope, and the average fluorescence intensity was calculated using ImageJ.
[0105] The experimental results are shown in Table 5.
[0106] Table 5. Effects of different prescription combinations on keloids
[0107]
[0108]
[0109] Table 5 shows that scar tissue formation is related to abnormally activated myofibroblasts, leading to extracellular matrix sclerosis and scar formation. TGF-β is a major cytokine stimulating myofibroblast differentiation; the addition of fibers significantly reduced TGF-β levels compared to the microsphere group alone. Furthermore, the α-SMA expression in the microsphere + fiber + matrix combination was significantly reduced, indicating decreased fibroblast differentiation into myofibroblasts, which is beneficial for reducing scar formation.
[0110] In summary, compared to microspheres + matrix alone, the combination of microspheres + fibers + matrix with specific ratios and sizes significantly reduced the inflammatory response. Although the fiber + matrix combination resulted in the lowest inflammation, it was insufficient to stimulate further collagen production. Compared to microspheres + matrix alone or fibers + matrix alone, the combination of microspheres + fibers + matrix with specific ratios and sizes significantly increased the total amount of collagen produced, with the type I / III ratio closer to normal skin. Compared to microspheres + matrix alone, the combination of microspheres + fibers + matrix with specific ratios and sizes significantly reduced TGF-β, producing only a mild stimulating effect. This not only facilitated collagen secretion by fibroblasts but also significantly reduced the risk of fibroblast differentiation into myofibroblasts, thus reducing scar formation. Compared to microspheres + matrix alone or fibers + matrix alone, the combination of microspheres + fibers + matrix with specific ratios and sizes significantly reduced α-SMA expression, thus reducing keloid formation. In conclusion, the microsphere + fiber + matrix combination has significant advantages as a filler, and the microspheres and fibers in this combination have a significant synergistic effect on total collagen production.
Claims
1. An injectable filler that stimulates collagen regeneration and remodeling, characterized in that, The filler is mainly composed of microspheres, fibers, and matrix materials; the microspheres are made of polytrimethylene carbonate, the fibers are made of polycaprolactone and polytrimethylene carbonate; and the matrix material is hyaluronic acid hydrogel. The microspheres are spherical with a particle size of 25-60 μm; the fibers are rod-shaped with a diameter of 50 μm-150 μm and a length of 300 μm-700 μm. The mass ratio of the microspheres, fibers, and matrix material is 10:1:
500.
2. The injectable filler that stimulates collagen regeneration and remodeling according to claim 1, characterized in that, The filler further includes water, isotonic agents, pH adjusters, and analgesics.
3. A method for preparing an injectable filler that stimulates collagen regeneration and remodeling as described in claim 1, characterized in that, Includes the following steps: Microsphere preparation methods include emulsification-crosslinking, spray drying, electro-spraying, or microfluidics; Fiber preparation methods include electrospinning, melt spinning, extrusion spinning, grinding, microfluidic spinning, or bioprinting. The preparation methods for matrix materials include physical crosslinking or chemical crosslinking. The fibers and microspheres are added to the matrix material and thoroughly mixed to obtain the final product.
4. The preparation method according to claim 3, characterized in that, The electrospinning method mentioned is the near-field electrospinning method.
5. The preparation method according to claim 3, characterized in that, The grinding method is an airflow pulverization method.
6. The preparation method according to claim 3, characterized in that, The chemical crosslinking method is a free radical homopolymerization or copolymerization method, a radiation method, or a photopolymerization method.
7. The method for preparing the injectable filler that can stimulate collagen regeneration and remodeling according to claim 3, characterized in that, Includes the following steps: (1) Microsphere preparation: Polytrimethylene carbonate is dissolved in an organic solvent and ultrasonically mixed to form an oil phase. The oil phase is added dropwise to a polyvinyl alcohol aqueous solution and stirred and emulsified at 300-800 rpm for 2-8 hours. After the organic solvent in the solution is evaporated, the microspheres are washed, freeze-dried, and passed through a sieve to obtain the microspheres. (2) Fiber preparation: Polycaprolactone solution and polytrimethylene carbonate solution are mixed together to form the required electrospinning suspension. The suspension is electrospinned at a working distance of 10~20 cm, a voltage of 8~13 kV, and a syringe pump speed of 0.5~1.2 mL / h to obtain a fiber membrane. The electrospinned fiber membrane is frozen in liquid nitrogen for 10~20 minutes and broken into fibers with a high-speed stirrer. The fibers are obtained by passing them through a sieve. (3) Preparation of matrix material: Weigh hyaluronic acid, dissolve it in sodium hydroxide solution, add 1,4-butanediol diglycidyl ether, heat at a constant temperature of 40~60℃, stir at a speed of 100~400 rpm for 1~4 hours to crosslink the gel, adjust the pH to neutral, dialyze to purify, freeze dry and then reconstitute to obtain the matrix material; (4) Mixing: Add the fibers and microspheres to the matrix material and stir thoroughly to obtain the final product.
8. The use of the injectable filler of claim 1, which can stimulate collagen regeneration and remodeling, in the preparation of medical aesthetic, plastic surgery, filling and tissue defect repair materials.
Citation Information
Patent Citations
Stimulus-responsive injectable composite drug-loaded hydrogel and preparation method thereof
CN116327687A
Implantable materials for bone repair
US20130244942A1